2000
DOI: 10.1002/1521-3757(20000901)112:17<3234::aid-ange3234>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

A Light-Modulated Sequence-Specific DNA-Binding Peptide

Abstract: Packende Verbindungen! Zwei Monomere eines bZIP‐Proteins wurden an den basischen Bereichen über eine photoempfindliche Azobenzoleinheit zu einem Homodimer verknüpft. Dieses Dimer kann nach Bestrahlung mit Licht geeigneter Wellenlänge isomerisiert werden, wobei die beiden Isomere mit einer geringen (trans) oder hohen Affinität (cis) in der großen Furche der DNA binden (siehe Bild). BB=basische Bereiche, ds=Doppelstrang.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…[23][24][25] In our studies reported herein, we applied AFM singlemolecule force spectroscopy to study the specific binding between the peptides listed in Table 1 and the DNA target sequence. Each peptide was covalently immobilized to an amino-functionalized mica surface in a directed manner with the short C-terminal linker 1,8-diamino-3,6-dioxaoctane and the cross-linker BS 3 (bis(sulfosuccinimidyl)suberate; Figure 1 b). This immobilization prevents unfolding of the peptide caused by physisorption on the surface.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…[23][24][25] In our studies reported herein, we applied AFM singlemolecule force spectroscopy to study the specific binding between the peptides listed in Table 1 and the DNA target sequence. Each peptide was covalently immobilized to an amino-functionalized mica surface in a directed manner with the short C-terminal linker 1,8-diamino-3,6-dioxaoctane and the cross-linker BS 3 (bis(sulfosuccinimidyl)suberate; Figure 1 b). This immobilization prevents unfolding of the peptide caused by physisorption on the surface.…”
mentioning
confidence: 82%
“…In this way, cell growth, differentiation, and development are regulated. The possibility to influence and control cell metabolism through modified synthetic transcription factors [1][2][3][4] offers fascinating prospects for molecular cell biology in the framework of biomimetics and synthetic biology. [5,6] The design and synthesis of biologically active artificial enzymes and new protein-based materials can be investigated by the combination of bioorganic bottom-up synthesis and single-molecule affinity nanotechnology.…”
mentioning
confidence: 99%
“…Particularly relevant are those based on dimeric bZIP basic regions, in which the natural C/C-terminal leucine zipper is replaced by artificial dimerizers [14][15][16][17] . Some of these designs have gone even further and incorporate switchable elements that allow conditional off/on DNA binding by the application of external stimuli such as light or metal ions [18][19][20][21][22] . Despite advances in these and other switchable DNA binders 23,24 , designed systems capable of interacting with alternative DNA sites in an externally regulated manner are unknown.…”
mentioning
confidence: 99%
“…In pioneering work, Mascarenas and co-workers used an azobenzene-based cross-linker to artificially dimerize the basic regions of GCN4 (20). Artificially dimerized GCN4 basic regions have been shown to be capable of specific and high-affinity recognition of native GCN4 DNA-binding sites (21,22).…”
mentioning
confidence: 98%
“…The cis photoisomer was found to bind DNA more tightly than the trans isomer by gel-shift analysis. However, DNA binding was found to inhibit the cis f trans photoisomerization (and thermal isomerization) process (20). We now report a different approach, the incorporation of an azobenzene cross-linker into the leucine zipper region of bZIP-GCN4, that results in reversible photocontrol of GCN4 DNA-binding ability.…”
mentioning
confidence: 99%